30 years of free‐air carbon dioxide enrichment (FACE): What have we learned about future crop productivity and its potential for adaptation?. (2nd November 2020) - Ainsworth, Elizabeth A.; Long, Stephen P.
Abstract: Free‐air CO2 enrichment (FACE) allows open‐air elevation of [CO2 ] without altering the microclimate. Its scale uniquely supports simultaneous study from physiology and yield to soil processes and disease. In 2005 we summarized results of then 28 published observations by meta‐analysis. Subsequent studies have combined FACE with temperature, drought, ozone, and nitrogen treatments. Here, we summarize the results of now almost 250 observations, spanning 14 sites and five continents. Across 186 independent studies of 18 C3 crops, elevation of [CO2 ] by ca. 200 ppm caused a ca. 18% increase in yield under non‐stress conditions. Legumes and root crops showed a greater increase and cereals less. Nitrogen deficiency reduced the average increase to 10%, as did warming by ca. 2°C. Two conclusions of the 2005 analysis were that C4 crops would not be more productive in elevated [CO2 ], except under drought, and that yield responses of C3 crops were diminished by nitrogen deficiency and wet conditions. Both stand the test of time. Further studies of maize and sorghum showed no yield increase, except in drought, while soybean productivity was negatively affected by early growing season wet conditions. Subsequent study showed reduced levels of nutrients, notably Zn and Fe in most crops, and lower nitrogen and protein in the seeds of non‐leguminous crops. Testing across crop germplasm revealed sufficient variation to maintain nutrient content under rising [CO2 ]. A strong correlation of yield response under elevated [CO2 ] to genetic yield potential in both rice and soybean was observed. Rice cultivars with the highest yield potential showed a 35% yield increase in elevated [CO2 ] compared to an average of 14%. Future FACE experiments have the potential to develop cultivars and management strategies for co‐promoting sustainability and productivity under future elevated [CO2 ]. Abstract : Lessons from more than 250 experiments, with 15 field crops on five continents using free‐air CO2 enrichment (FACE). Plus, its combination with drought and nitrogen, and with rising ozone and temperature.